Penerapan Model Pembelajaran Berbasis Masalah Materi Kelainan Sistem Gerak pada Manusia terhadap Hasil Belajar Siswa Kelas XI MA - Annisa, Sholihatun; Putra, Aminuddin Prahatama; Ajizah, Aulia (BIO-EDU: Jurnal Pendidikan Biologi, 2024)
The purposes of this research were to (1) describe the effect of the application of the problem-based learning model on cognitive learning outcomes of class XI MA students in the matter of Movement System Disorders in Humans, (2) describes the affective and psychomotor learning outcomes of class XI MA students on the subject of Movement System Disorders in Humans using the problem-based learning model. The subjects of this study were students of class XI IPA 2 and XI IPA 3 MAN 3 Banjarmasin. The research method used was quasi-experimental to determine the effect of the problem-based learning model on cognitive, affective, and psychomotor learning outcomes. The research results show (1) The application of the problem-based learning model to material of Movement System Disorders in Humans has a significant effect on the learning outcomes of class XI MA students, namely a symptom sig (2-tailed) value < 0.05, which is 0.000 and the result of cognitive learning processes with the application of the problem-based learning model is in the good category, (2) the affective learning outcomes of student character behavior and social behavior are include in the good to very good category and psychomotor learning outcomes with the application of the problem-based learning model are in the good category. Through this research, we found that there was an effect of applying the problem-based learning model on the subject of Movement System Disorders in Humans on the learning outcomes of class XI MA students